Pharmacologic Management of Monogenic and Very Early Onset Inflammatory Bowel Diseases - Anne E. Levine; Dominique Mark; Laila Smith; Hengqi B. Zheng; David L. Suskind (MDPI AG, 2023)
Inflammatory bowel disease (IBD) is treated with a variety of immunomodulating and immunosuppressive therapies; however, for the majority of cases, these therapies are not targeted for specific disease phenotypes. Monogenic IBD with causative genetic defect is the exception and represents a disease cohort where precision therapeutics can be applied. With the advent of rapid genetic sequencing platforms, these monogenic immunodeficiencies that cause inflammatory bowel disease are increasingly being identified. This subpopulation of IBD called very early onset inflammatory bowel disease (VEO-IBD) is defined by an age of onset of less than six years of age. Twenty percent of VEO-IBDs have an identifiable monogenic defect. The culprit genes are often involved in pro-inflammatory immune pathways, which represent potential avenues for targeted pharmacologic treatments. This review will provide an overview of the current state of disease-specific targeted therapies, as well as empiric treatment for undifferentiated causes of VEO-IBD.